2013
DOI: 10.1074/mcp.m112.026914
|View full text |Cite
|
Sign up to set email alerts
|

Wnt3a-dependent and -independent Protein Interaction Networks of Chromatin-bound β-catenin in Mouse Embryonic Stem Cells

Abstract: Canonical Wnt signaling is repeatedly used during development to control cell fate, and it is often implicated in human cancer. ␤-catenin, the effector of Wnt signaling, has a dual function in the cell and is involved in both cell adhesion and transcription. Nuclear ␤-catenin controls transcription through association with transcription factors of the TCF family and the recruitment of epigenetic modifiers. In this study, we used a strategy combining the genetic manipulation of mouse embryonic stem cells with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 58 publications
(30 reference statements)
1
14
0
Order By: Relevance
“…The pathway is often found activated in a variety of cancers, either through activating mutations in β-catenin itself or in proteins involved in Wnt-signaling (Morin, 1999 ; Macdonald et al, 2009 ). Pontin and Reptin possess opposing regulatory functions in this pathway (Bauer et al, 1998 , 2000 ; Yakulov et al, 2013 ) (Table 2 ). The ATPases were shown in vitro to directly interact with β-catenin in the same region, and thus might exhibit competitive binding (Bauer et al, 1998 , 2000 ).…”
Section: Role Of Pontin/reptin In Specific Cellular Pathwaysmentioning
confidence: 99%
“…The pathway is often found activated in a variety of cancers, either through activating mutations in β-catenin itself or in proteins involved in Wnt-signaling (Morin, 1999 ; Macdonald et al, 2009 ). Pontin and Reptin possess opposing regulatory functions in this pathway (Bauer et al, 1998 , 2000 ; Yakulov et al, 2013 ) (Table 2 ). The ATPases were shown in vitro to directly interact with β-catenin in the same region, and thus might exhibit competitive binding (Bauer et al, 1998 , 2000 ).…”
Section: Role Of Pontin/reptin In Specific Cellular Pathwaysmentioning
confidence: 99%
“…β-catenin is one of the best studied oncoproteins and diverse β-catenin protein-protein interactions have been identified. Recent studies, for example, have revealed the association of β-catenin with chromatin and epigenetic modifying complexes (4,5), and it is clear that our knowledge of β-catenin protein function is quite incomplete.…”
Section: Introductionmentioning
confidence: 99%
“…Mouse ESCs [28,29] were cultured in DMEM supplemented with 15% FCS, penicillin, streptomycin, glutamine, non-essential amino acids, sodium pyruvate, β-mercaptoethanol and LIF (in-house produced). P19 cells [30] were cultured in DMEM supplemented with 10% FBS, penicillin, streptomycin, glutamine and non-essential amino acid.…”
Section: Methodsmentioning
confidence: 99%